Electrochemiluminescent screening for methamphetamine metabolites. Issue 10 (16th April 2021) - Dokuzparmak, Emre; Brown, Kelly; Dennany, Lynn
Abstract : The abuse of methamphetamine (MA) is to date detected and subsequently verified through the monitoring of MA and its metabolites within biological specimens. Abstract : The abuse of methamphetamine (MA) is to date detected and subsequently verified through the monitoring of MA and its metabolites within biological specimens. Current approaches require complex sample purification strategies alongside significant analysis time. Given the high prevalence of MA within the global drug market, there remains a need for rapid, portable and alternative screening approaches appropriate for direct detection within biological matrices for employment across the forensic and clinical environments. This contribution illustrates the use of an electrochemiluminescence (ECL) strategy for the screening of MA, amphetamine (AMP) and para hydroxy-methamphetamine ( p OH-MA) for such applications. The sensing system showed ideal analytical performance with linear ranges at forensically relevant concentrations of 0.1 μM to 0.5 mM for MA, 10 μM to 1 mM AMP and 10 μM to 5 mM for p OH-MA, and superb detection limits of 74.6 nM, 6 μM and 82. μM for MA, AMP and p OH-MA respectively. Furthermore, the sensor was successful in the detection of MA, AMP and p OH-AMP within human pooled serum, artificial urine and saliva, without any prior purification strategies. Here a portable ECL sensor is detailed for the successful employment of the direct screening of these amphetamine type substances and their corresponding metabolites at clinically and forensically relevant concentrations within a range of biological matrices. This approach successfully represents a strong proof-of-concept, for a novel, simple and rapid screening method with significant potential for high-throughput screening of biological samples for drug metabolites, widening the avenues where ECL sensors could be employed.